Effects of 6 Months of Exercise‐Based Cardiac Rehabilitation on Autonomic Function and Neuro‐Cardiovascular Stress Reactivity in Coronary Artery Disease Patients. Issue 17 (3rd September 2019) - Badrov, Mark B.; Wood, Katelyn N.; Lalande, Sophie; Sawicki, Carolyn P.; Borrell, Lindsay J.; Barron, Carly C.; Vording, Jennifer L.; Fleischhauer, Arlene; Suskin, Neville; McGowan, Cheri L.; Shoemaker, J. Kevin
Abstract : Background: Autonomic dysregulation represents a hallmark of coronary artery disease (CAD). Therefore, we investigated the effects of exercise‐based cardiac rehabilitation (CR) on autonomic function and neuro‐cardiovascular stress reactivity in CAD patients. Methods and Results: Twenty‐two CAD patients (4 women; 62±8 years) were studied before and following 6 months of aerobic‐ and resistance‐training–based CR. Twenty‐two similarly aged, healthy individuals (CTRL; 7 women; 62±11 years) served as controls. We measured blood pressure, muscle sympathetic nerve activity, heart rate, heart rate variability (linear and nonlinear), and cardiovagal (sequence method) and sympathetic (linear relationship between burst incidence and diastolic blood pressure) baroreflex sensitivity during supine rest. Furthermore, neuro‐cardiovascular reactivity during short‐duration static handgrip (20s) at 40% maximal effort was evaluated. Six months of CR lowered resting blood pressure ( P <0.05), as well as muscle sympathetic nerve activity burst frequency (48±8 to 39±11 bursts/min; P <0.001) and burst incidence (81±7 to 66±17 bursts/100 heartbeats; P <0.001), to levels that matched CTRL and improved sympathetic baroreflex sensitivity in CAD patients ( P <0.01). Heart rate variability (all P >0.05) and cardiovagal baroreflex sensitivity ( P =0.11) were unchanged following CR, yet values were not different pre‐CR from CTRL (all P >0.05). Furthermore, before CR, CAD patients displayed greater blood pressure and muscle sympathetic nerve activity reactivity to static handgrip versus CTRL (all P <0.05); yet, responses were reduced following CR (all P <0.05) to levels observed in CTRL. Conclusions: Six months of exercise‐based CR was associated with marked improvement in baseline autonomic function and neuro‐cardiovascular stress reactivity in CAD patients, which may play a role in the reduced cardiac risk and improved survival observed in patients following exercise training.